Expanding the role of mobile apps in preventing hyperphosphatemia in patients undergoing haemodialysis: A systematic review and meta-analysis - Hibatulloh, Muhammad Farhan; Amini, Stefia Aisyah; Putri, Dhiani Eka; Rachmawati, Dwita Aryadina (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Improper diets of patients with chronic kidney disease undergoing hemodialysis are likely to develop hyperphosphatemia, which can also result in other complications such as lacking of calcium and protein. Meanwhile, dietary management using Mobile Apps can provide specific diet programs for every patient to control nutrition.Objectives: This review aims to identify the effectiveness of Mobile App based self-management dietary program to control phosphate, calcium, and albumin level for patients with hemodialysis.Methods: This systematic review and meta-analysis follows PRISMA (Preferred Reporting Items for Systematic and Meta-Analysis) Guideline. Study selection was done using several electronic databases such as PubMed, Cochrane Library, ScienceDirect, Springer, EBSCO, EMBASE, Google Scholar, Proquest, SAGE, Taylor & Francis, and SCOPUS. Bias risk was analyzed with Cochrane Risk of Bias 2.0 Tool, then meta-analysis was made using Review Manager V5.4.Results:This study included 5 randomized controlled studies that were later interpreted with meta-analysis. Based on the result, there are significant effect for phosphate level reduction (pooled MD -0.63, 95% CI [-1.18,-0.08], p=0.02, I2=82%) and calcium level increase (pooled MD=-0.51, 95% CI [-0.77,-0.24], p=0.0002, I2=0%). Meanwhile, there is no significant change in albumin level (pooled MD=-0.09, 95% CI [-0.33,0.16], p=0.49, I2=0%).Conclusions: In conclusion, mobile App based self-management diet significantly reduces phosphate level and is likely to maintain albumin level for hemodialysis patients. This intervention also has the potential to increase calcium levels to prevent bone disease.